ASME 2008 6th International Conference on Fuel Cell Science, Engineering and Technology 2008
DOI: 10.1115/fuelcell2008-65177
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Performance Evaluation of a High Temperature PEM Fuel Cell at Different Temperatures and Pressures

Abstract: The high temperature proton exchange membranes (HT-PEM) attract growing interests due to its enhanced electrochemical kinetics, simplified pinch technology and utilization of higher CO-rich reformed hydrogen as the fuel. From the technological point of view, using pure hydrogen as fuel seems highly restrictive because hydrogen with high purity may not always be readily available. As an attractive alternative to compressed hydrogen, it is preferred to use hydrogen-rich gases as fuel. On-site generation of hydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Hence, equation ( 3) is one of the multiple regression models we may recommend for use in the description of the dependence of the yield V from all the predictors, together with the model (1), irrespective of the fact that some non-significant components are included in it. The above discussed models do indicate a positive dependence of V on the temperature factor T, the increase of the temperature by 1 o C will increase on the average, the yield by 0.981 mV for model (3) and by 0.962 mV in model (1).…”
Section: Statistical Analysis and Resultsmentioning
confidence: 78%
“…Hence, equation ( 3) is one of the multiple regression models we may recommend for use in the description of the dependence of the yield V from all the predictors, together with the model (1), irrespective of the fact that some non-significant components are included in it. The above discussed models do indicate a positive dependence of V on the temperature factor T, the increase of the temperature by 1 o C will increase on the average, the yield by 0.981 mV for model (3) and by 0.962 mV in model (1).…”
Section: Statistical Analysis and Resultsmentioning
confidence: 78%
“…During operation, voltage and current are the two most important parameters one must know to evaluate the performance of a fuel cell. Increasing temperature tends to improve the performance of the fuel cell as it overcomes activation polarization, but higher temperatures also accelerate degradation processes, as presented in [18,19]. In parallel with the experimental data, models have been developed to study the phenomena of interest such as the influence of the charge double layer [20], or the distribution of current and gases in the flow channels [21].…”
Section: Introductionmentioning
confidence: 99%
“…They operate at higher temperatures from 120-180 o C and exhibit stable voltage output at steady state conditions. The HT-PEMFC is credited with faster electrochemical kinetics, improved water management and carbon monoxide tolerance, J. Zhang et al (1), E. Ubong et al (2) and S. Das et al(3). As a result of the low electro-osmotic drag and the good proton conductivity of the PBI membrane, the fuel cell design and the routine maintenance could also be significantly simplified, J.T.…”
Section: Introductionmentioning
confidence: 99%
“…The ease of using high temperature fuel cells operating above 140 o C currently receives wide attention because light hydrocarbon fuels (alcohol, natural gas, propane) are viewed as future candidates for PEMFC application. E. Ubong et al (2) conducted an experimental work on HT-PEMF and evaluated the polarization and power density curves as a function of temperature, pressure and air stoichiometry. S. Das et al(3) reported on a 2-5% CO mixture in hydrogen with a BASF HT-PEM membrane.…”
Section: Introductionmentioning
confidence: 99%